Tujuan Hidup Manusia Menurut Advaita Vedanta Dan Pengaruh Era Globalisasi - Kadek Widiastuti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Humans are thinking creatures (homo sapiens), the ability to think is what distinguishes humans from other creatures and elevates humans as God's most perfect creatures in the universe. The ability to think humans can help themselves from the burdens of life. Humans from generation to generation develop their minds so that they can make it easier for them to carry out their daily activities. Darsana as a philosophical system which means a view of something has 6 streams, one of which is Vedanta Darsana. Vedanta or Uttara Mimamsa is the culmination of philosophy based on the teachings of the Upanishads, one of the three schools of Vedanta is Advaita Vedanta. The purpose of life according to Advaita Vedanta is important for Hindus to understand in order to have guidelines or directions in living life. The current era of globalization does not only have a positive impact, but also has a negative impact on human life, especially in terms of determining life goals.